Variability of yield and yield components of 23 hybrid cayenne pepper (Capsicum frutescens) genotypes under shaded and unshaded conditions (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Putri DRM, Syukur M, Ritonga AW. 2025. Variability of yield and yield components of 23 hybrid cayenne pepper (Capsicum frutescens) genotypes under shaded and unshaded conditions. Biodiversitas 26: 396-406. Cayenne pepper production is challenged by limited agricultural land, necessitating a sustainable intercropping system to meet rising demand. This requires varieties that can grow, develop, and produce under shade-stress conditions. This study aimed to obtain information on the variability of growth, yield components, and physiological traits and to determine yield-related traits in cayenne pepper hybrids obtained from full-diallel crosses under shaded and unshaded conditions. A total of 23 genotypes, consisting of 20 F1 hybrids from five parental lines and three comparisons, were planted using a nested randomized complete block design with two factors: shade and genotype. The results showed that G8 and G27 exhibited superior performance under shade conditions, producing a higher number of fruits per plant, fruit yield per plant, marketable number of fruits, marketable yield fruit, fruit diameter, and fruit weight compared to unshaded conditions. These findings have practical implications for cayenne pepper production, as they can guide the selection of varieties for shaded conditions. Chili was categorized into six clusters under unshaded conditions and four clusters under shaded conditions. Marketable yield fruit, marketable number of fruits, and number of fruits per plant had a significant positive correlation coefficient on fruit yield per plant under unshaded conditions. In contrast, under shaded conditions, there was a significant positive correlation shown on fruit diameter, plant height, marketable yield fruit, number of fruits per plant, marketable number of fruits, and fruit weight.
Keywords: cayenne pepper hybrid; full diallel; yield; shade stress; tolerant genotype